In-service Education for Psychiatric Nurses based on the Technological Competency as Caring in Nursing Theory - Osaka, Kyoko; Blaquera, Allan Paulo; Soriano, Krishan; Betriana, Feni; Kataoka, Mutsuko; Tanioka, Tetsuya (Celebes Nursing Journal, 2024)
Introduction: One of the strategies that can be used to improve the quality of psychiatric care is the development and dissemination of a new in-service education program based on the use of technologies for both psychiatric nurse managers and nurses. Objective: This discussion paper aimed to report on in-service education for improving the quality of psychiatric nursing care based on the Technological Competency as Caring in Nursing (TCCN) theory for psychiatric nurse managers and staff nurses. Method: Relevant articles related to psychiatric nursing care, in-service education, technologies in nursing, and caring in nursing were retrieved, analyzed, discussed, and developed. Result: The use of in-service education programs based on the TCCN is expected to become a practical approach to incorporating new technologies into quality psychiatric care. Conclusion: Use of in-service education programs based on the TCCN theory is expected to become a practical approach to incorporating new technologies into quality psychiatric nursing care in the future.